EFFECT OF TEACHER MOTIVATION ON IMPPLIMENTATION OF MATHEMATCS CURRICULUM IN PRE PRIMARY SCHOOLS IN CENTRAL DIVISION, TRANS-NZOIA COUNTY, KENYA - Ruth, Onchera; Ngasike, Dr. John; Cherekes, Maurice K. (IJRDO- Journal of Educational Research, 2021)
Early childhood education provided the building block upon which the children develop socially, self-expression skills, communication skills and skills in mathematics. Motivation is a directional force that makes someone to behave in a certain manner. Okumbe (2013) still asserts that motivation is a process that takes place in within an individual and is psychological and cannot be seen directly but manifests itself in the way one behaves. It is agreed therefore that motivation comprises of all the inside situations explained as wishes or desired situation which activates the interests of a person to perform certain actions. Motivation has three main parameters; needs, drives and performance. Motivation therefore is that internal ability to make results look appealing intrinsic factors like having professional knowledge in the area; having an interest and being motivated are important characteristics in the implementation of the program and can also be a hindrance the implementation of the curriculum in a proper way if there are shortcomings in any of the areas. The purpose of this study was to determine the effect of teacher motivation on implementation of mathematics curriculum for pre-primary learners’ in central division, Trans-Nzoia County. The objectives of the study were; to determine the effect of teacher motivation and commitment on implementation of pre-primary learners’ mathematics curriculum in Trans-Nzoia County. The study employed skinners theory. Descriptive survey design was used. The sample size using Fishers formula was 112 respondents then simple random sampling and statured sampling were used to get target population to be used .74 ECDE(Early childhood development education) teachers, 36 primary head teachers, and 3educational officers. Pilot study to test reliability and validity of research instruments were above 0.70 cronbatch alphas. The instruments for data collection were the questionnaires and interview schedule. Quantitative data was analyzed using Statistical Package for Social Sciences version 27.0 and results presented using percentages, means, frequencies and p-values while qualitative data was analyzed using themes. The study findings indicated a significant relationship between teacher’s motivation and commitment on implementation of pre-primary mathematics curriculum. The study concluded that government should formulate a policy to always take into consideration teachers’ motivation and commitment when recruiting and promoting ECDE teachers’ .This study was important to inform the various ECDE educational stakeholders of the fundamental factors to consider for effective implementation of mathematics curriculum among the preprimary learners.